Buergers Disease (Thromboangiitis Obliterans): A Diagnostic Challenge-A Rare Case Report - Wadud, Md Armane; Taimur, Syed Dawood Md; Kabir, CM Shaheen; Roy, Siba Pada (BIRDEM Medical Journal, 2016)
Buergers disease or Thromboangiitis obliterans is a segmental inflammatory disease that affects the vessels and nerves of the extremities. It usually affects men below 45 years old and correlates with tobacco, as a predisposing factor. A young adolescent boy of 18 yrs, smoker, nonalcoholic, nondiabetic was presented with the complaints of progressive aching pain (Claudication pain) during walking in both legs which relives by taking rest for last 3 years and also suffering from long standing non healing ulcer in the right great toe and second toe following traumatic nail avulsion Birdem Med J 2015; 5(1): 37-41